Analis Pengukuran Kualitas Pengelolaan Rekam Medis Elektronik Menggunakan Metode Delone and McLean pada RSUD Dr. H. Mohamad Rabain - Sri Warianti; Tata Sutabri (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This Electronic Medical Record is a digital version of a medical record, the same as a paper-based manual medical record, this electronic medical record also contains information regarding health history, diagnoses, laboratory results, examination notes, medications given, medical procedures, and other data. relevant to the patient's health condition. It is hoped that the implementation of Electronic Medical Records can increase the efficiency of BPJS claims and improve the quality of service. Therefore, this study aims to analyze the use of RME using the Delone and Mclean method. The Delone and Mclean method is an information system quality evaluation framework that includes six dimensions, namely information system quality, information quality, service quality, use quality, user satisfaction, and user impact. In this study, we apply this method to analyze the quality of RME management. This research uses a quantitative approach by collecting data through questionnaires distributed to RME users in hospitals. The questionnaire measures user perceptions of information system quality, information quality, service quality, use quality, user satisfaction, and impact of using RME. The results of this research are expected to provide better insight into the use of RME in the context of work efficiency. The findings of this research will provide input for RME developers to improve the quality of information systems, the quality of information, and the quality of services provided to users. Apart from that, this research also contributes to theory and research in the field of information systems by applying the Delone and Mclean method in the context of RME management.